Clinical efficacy and imaging evaluation of recombinant tissue plasminogen activator thrombolytic therapy in patients with wake up stroke: A randomized controlled trial. Issue 36 (4th September 2020) - Zhang, Chun-Yang; Yang, Bin; Li, Dong-Mei; Shi, Qiu-Yan; Li, Hong; Li, Yan-Ling; Wang, Cui-Lan
Abstract: Introduction: Wake up stroke starts in sleep and is a more common form of ischemic stroke. At present, it is still controversial whether wake up stroke can be treated with thrombolytic therapy. Therefore, this study will combine imaging techniques to assess the onset time of wake up stroke patients, and to analyze the imaging characteristics of wake up stroke patients and patients suitable for thrombolytic therapy within the time window. Methods/design: This study will be a single-blinded, randomized controlled trial with 2 parallel groups. It will be conducted at North China University of science and technology affiliated hospital. Discussion: There is no consistent conclusion about the pathogenesis of wake up stroke. Wake up stroke is more likely to manifest as small vessel disease. The incidence of wake up stroke patients is relatively high, and the effectiveness and safety of intravenous thrombolysis under the guidance of multimode imaging therapy in wake up stroke need to be further explored by prospective, large-scale studies. Trial registration: ClinicalTrials.gov, ChiCTR2000034402, Registered on 05 July 2020